The Effect of Using Circular Training on Developing Maximum Strength and Performing the Skill of Overwhelming Beating among Young Volleyball players - Assistant Prof. Dr. Ali Hameed Ali AlZubaidi (Zien Journals, 2023)
The study aimed to identify the effect of using circular training in developing the maximum strength of the muscles of the legs and arms, among the players of Kufa Sports Club, as well as identifying the effect of using circular training in improving the accuracy of performance for the skill of overwhelming beating, the researcher used the experimental method in the method of pre- and post-measurement, as the number of training units reached (12) weeks and the research sample of (20) players representing Kufa Sports Club in volleyball. The players were divided into two groups of equal number, the first group experimental and the second group control, the researcher used the statistical bag to know the results of the search (SPSS), the results of the study showed that circular training has an effective impact on the development of (maximum strength of the muscles of the legs and arms), and contributed to improving the accuracy of performance of the skill of overwhelming beating, the researcher recommended the need to pay attention to physical and skill variables for their importance in raising the level of performance of players, the study also recommended circulating the results of the study to the rest of the Iraqi club players to raise the physical and skill responses of volleyball players
Keywords: circular training; maximum strength; overwhelming beating